Study and modeling of the thrombosis of small cerebral aneurysms, with and without flow diverter, by the lattice Boltzmann method. (May 2023) - Mezali, Farouk; Naima, Khatir; Benmamar, Saida; Liazid, Abdelkrim
Highlights: Clotting model in aneurysms with and without flow diverter devices have been studied. Thrombosis is modeled by the "fluid age" model through the lattice Boltzmann method. Thrombosis prediction model was tested on three aneurysms with stents. Rate occlusion is between 80% to 91% for a medium and large aspect ratio aneurysms. For very small aneurysms, aneurism occlusion is low. Abstract: Background and objective: Small cerebral aneurysms are currently commonly treated non-invasively by flow diverter device. These stents lead to thrombotic occlusion of the aneurysm soon after their placement. The purpose of this work is to model clotting into intracranial aneurysms with and without stents, using a non-Newtonian of blood behavior, and to investigate the importance of stent to generate desired thrombus in intracranial aneurysms. Method: The description of blood flow is made by the Boltzmann lattice equations, while thrombosis is modeled by the "fluid age" model. The lattice Boltzmann method is a computational technique for simulating fluid dynamics. The method is based on a mesoscopic approach, where the fluid is represented by a set of particles that move and interact on a grid. The model for blood coagulation is described by lattice Boltzmann Method, and it doesn't take into account the complicated coagulation pathway, this main idea is developed using the model of residence time of blood: all fluid in the domain is assumed to be capable of clotting, given enough time. The fluid age is measured by a passive scalar using a transport equation, and the node coagulates if the fluid age increases enough. Three small aneurysms of different sizes and shapes with three stents of various porosities were used to test the ability of the model to predict thrombosis. The "occlusion rate" parameter is used to assess the effectiveness of the flow diverter device. Results: For the large aspect ratio factor, the occlusion is: 91% for flow diverter devise with seven struts. For medium aspect ratio, a rate of 80% is achieved. An occlusion rate of slightly more than 30% is obtained for very small aneurysms with low aspect ratio. The Newtonian model underestimates the volume of thrombosis generated. The difference in the prediction of the thrombosis volume between the Newtonian and no-Newtonian Carreau-Yasuda models is approximately 10%. Conclusion: The occlusion rate is proportional to the aspect ratio form factor. For the large and medium aspect ratio factors, the occlusion is satisfactory. Concerning very small aneurysms with low aspect ratio, aneurysm occlusion is low. This rate can be improved to almost complete occlusion if the flow diverter device is doubled. The generality of the model suggests its extensibility toward any other type of thrombosis (stenosis, thrombosis in aortic aneurysms).